Correlation of Fibroblast Growth Factor-23 Levels with Hand Grip Strength in Twice Weekly Hemodialysis Patients - Aida Lydia; Donnie Lumban Gaol; Suhardjono; Murdani Abdullah (Jurnal Penyakit Dalam Indonesia)
Introduction. One of the main factors involved in bone mineral and musculoskeletal disorders in patients with chronic kidney disease (CKD) is fibroblast growth factor-23 (FGF-23). Fibroblast growth factor 23 (FGF-23) levels are elevated in hemodialysis patients. Despite FGF-23 associated left ventricular hypertrophy, there are no prior studies assessing whether FGF-23 level is associated with skeletal muscle strength in hemodialysis patient. This study aimed to determine the correlation between hand-grip strength (HGS) and FGF-23 levels in patients undergoing twice weekly hemodialysis patients.